Effect of selected weeds and organic emulsions on seed germination, seedling growth and biochemical content in rice (Oryza sativa) - S, BANJARE; V K, TRIPATHI; A, DIXIT; A K, VERMA (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2021–22 at ICAR-National Institute of Biotic Stress Management, Raipur, Chhattisgarh, to understand the allelopathic impact of 4 selected weeds and 2 organic products on germination, seedling growth and biochemical content in rice in laboratory condition in a completely randomized design (CRD). The results indicate that 15% solution of Ascophyllum nodosum extract (T15) and 15% solution of Medicago denticulate extract (T18), inhibits the germination by 78.72 and 40.42%, respectively and 5% solution of Moringa oleifera extract (T4), 5% solution of Parthenium hysterophorus extract (T1) and 15% solution of vermiwash (T9) increased the germination by 25.53, 23.41, and 21.28% respectively as compared to control. Treatment T4 and T9 increased the seedling’s vigour by 112.8 and 109.08%, while among them treatments, viz. 15% solution of A. nodosum extract (T15) and 15% solution of M. denticulate extract (T18) decreased the vigourness by -88.60% and -59.05% respectively. Treatment T4 and 5% solution of vermiwash (T7) increased the biochemical content by 17.79% and 13.49% respectively, while 15% solution of panchgavya (T2), and treatment T15 were significantly decreased the biochemical content by 39.26 and 42.33% respectively. Based on findings, it may be concluded that negative correlation was found between the response of rice crop and increasing concentrations of weed extracts and panchgavya unlike vermiwash. But lower concentration of M. oleifera and vermiwash showed most positive impact on rice seedlings.